1991
DOI: 10.1590/s0074-02761991000600041
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial chemotherapy with natural products and chemically defined molecules

Abstract: In the present work we have described the in vivo antimalarial activity of six different plants. Two of them (Vernonia brasiliana and Eupatorium squalidum) were tested in a randomic approach among 273 crude extracts from plants; four (Acanthospermum australe, Esenbeckia febrifuga, Lisianthus speciosus and Tachia guianensis) were selected after screening 22 crude extracts from different medicinal plants used in Brazil against fever and/or malaria. We also studied chemically defined molecules and some of them sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…For some plant families, the activity is related with specific compounds already shown to have antiplasmodial activity; this is the case of the indole alkaloids in Apocynaceae (Coutinho et al, 2013;Spencer et al, 1947), the diterpene phorbol esters in Euphorbiaceae, the acridone alkaloids in Rutaceae, the quassinoids in Simaroubaceae, and the sesquiterpene lactones and polyacetylenes in Asteraceae (Andrade-Neto et al, 2004b;Carvalho and Krettli, 1991a;Wright an Phillipson, 1990). The botanical families highlighted in this study are also found in other countries such as in West and South Africa (Clarkson et al, 2004;Zirihi et al, 2005) and are also used against malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some plant families, the activity is related with specific compounds already shown to have antiplasmodial activity; this is the case of the indole alkaloids in Apocynaceae (Coutinho et al, 2013;Spencer et al, 1947), the diterpene phorbol esters in Euphorbiaceae, the acridone alkaloids in Rutaceae, the quassinoids in Simaroubaceae, and the sesquiterpene lactones and polyacetylenes in Asteraceae (Andrade-Neto et al, 2004b;Carvalho and Krettli, 1991a;Wright an Phillipson, 1990). The botanical families highlighted in this study are also found in other countries such as in West and South Africa (Clarkson et al, 2004;Zirihi et al, 2005) and are also used against malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs were synthesized for the treatment of malaria, including amodiaquine, mefloquine, primaquine, derivatives of the quinoline moiety. More recently, the search for new drugs has been based on the exploitation of biodiversity including studies in the Amazon region (Brandão et al, 1985;Brandão et al, 1992aCarvalho et al, 1991a, and the ethnopharmacological approach has gained an increased attention (Willcox et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Parasites were maintained in continuous culture in A+ human erythrocytes using RPMI medium supplemented with 10% human serum, as described by Trager and Jensen (1976). The antiparasitic effect of the compounds was measured by growth inhibition percentages as described by Carvalho and Krettli (1991). Trophozoite-stages in sorbitol-synchronized blood (Lambros & Vanderberg 1979) were cultured at 1-2% parasitaemia and 2.5% haematocrit and then incubated with compounds (maximum 1 mg/mL in serial dilutions) diluted with a 0.02% final concentration of DMSO in the culture medium (RPMI 1640) for a total of 48 h at 37ºC.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Parasitic cultures were preserved in continuously A ?Ve human erythrocytes, using RPMI medium in complement with 10 % human blood serum, as described in the literature (Trager and Jensen, 1976). The antispasmodic effect of the compounds was measured by growth inhibition percentage as described by standard method described in literature (Carvalho and Krettli, 1991). In short, trophozoite stages in sorbitol-synchronized blood (Lambros and Vanderberg, 1979) were cultivated at 1-2 % parasitaemia and 2.5 % hematocrit and then incubated with the isolated compounds (maximum 1 mg/mL in serial dilutions), diluted with 0.…”
Section: Methodsmentioning
confidence: 99%